The Effect of Mild Traumatic Brain Injury on Cerebral Microbleeds in Aging - Toth, Luca; Czigler, Andras; Horvath, Peter; Szarka, Nikolett; Kornyei, Balint; Toth, Arnold; Schwarcz, Attila; Ungvari, Zoltan; Buki, Andras; Toth, Peter (Frontiers in Aging Neuroscience, 2021)
Traumatic brain injury (TBI) induces the formation of cerebral microbleeds (CMBs), which are associated with cognitive impairment, psychiatric disorders and gait dysfunction in patients. Elderly people frequently suffers TBI, especially mild brain trauma (mTBI). Interestingly, aging is an independent risk factor for the development of CMBs, as well. However, it is not well established how TBI and aging may interact to promote the development of cerebral microbleeds. In order to test the hypothesis that mild TBI exacerbates the development of cerebral microbleeds in the elderly we compared the number and cerebral distribution of CMBs assessed by analysing susceptibility weighted (SWI) magnetic resonance imaging (MRI) in young (24,65 +/- 10,22 year-old, n=18) and elder (71,86 +/- 7,31 year-old, n=17) patients after mTBI and in aged matched healthy subjects (young: 25,09 +/- 5,63 year- old, n=20; aged: 68,36 +/-4,88 year-old, n=23). We found significantly more CMBs in elder patients after mTBI compared to young patients, however, we did not observe a significant difference in the number of cerebral microhemorrhages between aged and aged + mTBI patients. The majority of CMBs were found supratentorially (lobar and basal ganglion). Lobar distribution of supratentorial CMBs showed that aging enhances the formation parietal and occipital CMBs after mild traumatic brain injury. This suggests that aging and mild traumatic brain injury do not synergize in the induction of the development of cerebral microbleeds and that different distribution of mTBI-induced CMBs in aged patients may lead to specific age-related clinical characteristics of mTBI.